The Effect of UV Aging on the Structure of PVC in the Presence of Organotin(IV) Compounds - Muna Bufaroosha,; Nadia Salih,; Angham G. Hadi,; Dina S. Ahmed,; Mohammed H. Al-mashhadani,; Emad Yousif, (Al-Nahrain Journal of Science, 2020)
New photostabilizers of poly(vinyl chloride) (PVC) were synthesized and investigated the photostabilizing efficiency of the polymer films by ultraviolet (UV) experiment. The rate of photodecomposition constant have been calculated for PVC films as a method for evaluating the efficiency of the organotin(IV) complexes that used as a photostabilizers after 300 hour of irradiation. The results have showed that the additives had reduced the rate of photodecomposition constant of PVC films significantly with comparison to PVC (blank). The (kd) value for PVC films was the highest in the absence of any additives, and the lowest value in the presence of triphenyltin (IV) complex.